Effects of Modified Sedang-Hwan added Hog Pancreas on the Experimental Diabetes of Rat induced by Streptozotocin - Chang-Geun Lee; Kyeong-Sun Soh; Chan-Gil Jeong (Korean Pharmacopuncture Institute, 2007)
Objectives : We performed this study in order to investigate the effects of Sedang-Hwan(世糖丸) and modified Sedang-Hwan(世糖丸變方)on the diabetes mellitus. Methods : We injected a vein with 65mg/kg of streptozotocin(STZ) on the rats. And then administered Sedang-Hwan(Sample 1 group); 18.7mg/kg/day, modified Sedang-Hwan; 16.5mg/kg/day(Sample 2 group) to Sample groups and observed the body weight, glucose and insulin levels. Results : 1. The Sample 1, 2 groups showed a high supppressive effect of body weight loss compared to Control group. 2. The Sample 1, 2 groups'glucose level showed a effective in lowering level compared to Control group. 3. The sample 1, 2 groups showed a higher insulin level than Control group. Conclusions : Conclusively, modified Sedang-hwan was recognized to have decrease effect of serum glucose of the diabetic rats induced by streptozotocin. It is also required to study on the further detailed mechanism of decrease effect of serum glucose by modified Sedang-hwan.